Occupational Segregation Based on Gender and Wage Inequality by Education, Age and Mobility (South Sumatra, Indonesia) - Arika Kurniawan; А. Azwardi; А. Yunisvita (Модернизация, инновация, развитие, 2021)
Purpose: this study measures gender segregation by occupations and wage inequality based on overall segregation, vertical segregation, and horizontal segregation in terms of labour supply, namely differences in wages, hours of work, age, level of education, and mobility (rural and urban) in South Sumatra Province in 2019.Methods: the data used in this study are secondary data sourced from the 2019 South Sumatra Province Labour Force Survey (SAK19.AK) which is limited to individuals aged 15 to 64 who are currently working, namely as many as 10,429 individuals, of whom 6,873 men and 3,556 women. Classification of the main occupations using quantitative analysis techniques, namely measuring segregation is based on the overall, vertical and horizontal dimensions based on the Gini coefficient, Somer D Statistic, and Pythagorean Theorem.Results: (1) Women are more segregated based on the main occupations, especially jobs with high social stratification and wage groups. (2) Women have more advantages in workplaces with low social stratification and higher education categories. (3) There is no wage inequality based on the main occupations, education, age, and mobility.Conclusions and Relevance: the results of the study prove that there is high segregation based on wage groups and educational composition. Women emphasize increasing education because based on vertical segregation, women with higher education level advantage more and they occupy jobs that are equal to men based on wage stratification.